‘“We’re getting the victory we fought for” we were told’: retrospective subjectivities in oral histories of Irish republicanism - Hepworth, J (Oral History Society, 2020)
This article draws upon twenty-two life-history interviews with Irish republican ex-combatants. Present-day republican fragmentation shapes retrospective subjective analysis. Oral histories today represent and reinforce imaginary binaries in the republican past, tapping into the politics of place and class as part of a broader discourse around the distribution of power within republicanism. Following linguist Mikhail Bakhtin’s conception of heteroglossia, these oral histories navigated republican leaders’ monological representations of republicanism and polyphonic micro-dynamics through the heterogeneous movement. Interrogating how interviews represented what Alessandro Portelli termed ‘the past in the present’, this article examines representations of milieux and power dynamics in oral histories which variously collapse and complicate the internal dynamics of Irish republicanism.